2016
DOI: 10.1186/s13023-016-0509-9
|View full text |Cite
|
Sign up to set email alerts
|

SPATA5 mutations cause a distinct autosomal recessive phenotype of intellectual disability, hypotonia and hearing loss

Abstract: We examined an extended, consanguineous family with seven individuals with severe intellectual disability and microcephaly. Further symptoms were hearing loss, vision impairment, gastrointestinal disturbances, and slow and asymmetric waves in the EEG. Linkage analysis followed by exome sequencing revealed a homozygous variant in SPATA5 (c.1822_1824del; p.Asp608del), which segregates with the phenotype in the family. Molecular modelling suggested a deleterious effect of the identified alterations on the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
0
15
0
6
Order By: Relevance
“…Pathogenic variants in SPATA5 have since been recognized to be associated with seizures and intellectual disability. 28,29…”
Section: Case 16mentioning
confidence: 99%
“…Pathogenic variants in SPATA5 have since been recognized to be associated with seizures and intellectual disability. 28,29…”
Section: Case 16mentioning
confidence: 99%
“…one heterozygous carrier) in the Exome Aggregation Consortium (ExAC) database [ 10 ]. The c.989_991del in-frame deletion has been previously reported in multiple patients with SPATA5- related disorder [ 1 3 ]. Both variants were confirmed by Sanger sequencing in both, Patients 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Autosomal recessive variants in the SPATA5 (spermatogenesis-associated protein 5, MIM: 613940) gene were recently associated with a specific disease phenotype. Tanaka et al [ 1 ], Kurata et al [ 2 ] and Buchert et al [ 3 ] reported 25 individuals with intellectual disability, microcephaly, hypotonia, spasticity, seizures, sensorineural hearing loss and cortical visual impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the following studies of SPATA5 have suggested a role of the SPATA5 gene not only in neuronal development but also in spermatogenesis. It was dominantly cytosolic in cortical neurons [33][34][35][36]. The SPATA5 deficiency affects mitochondrial morphology and inhibits mitochondrial dynamics, delays neuronal development, and is also associated with decreased cellular ATP [36].…”
Section: Discussionmentioning
confidence: 99%